Method for treating textile printing and dyeing wastewater by using rare earth modified Ti-based xerogel coagulant
By treating textile printing and dyeing wastewater by rare earth modified Ti-based xyrogel coagulant, the problems of large coagulant addition, large sludge emission, low efficiency of removing small molecule organic matter and low effluent pH in the prior art are solved, and efficient and stable wastewater treatment is achieved.
Patent Information
- Application Number
- CN202411625023.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-14
Smart Images

Figure CN119528294A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, in particular to a method for treating textile printing and dyeing wastewater by utilizing a rare earth modified Ti-based dry gel coagulant. Background Art
[0002] The textile printing and dyeing industry is a major emitter of industrial wastewater, which mainly contains dirt, grease, salts on textile fibers, and various slurries, dyes, surfactants, additives, acids and alkalis added during the processing. Among them, textile wastewater is mainly wastewater containing natural impurities, fats, starch and other organic substances generated during the cooking, rinsing, bleaching and sizing of raw materials. Printing and dyeing wastewater is generated in multiple processes such as washing, dyeing, printing and sizing, and contains a large amount of organic substances such as dyes, starch, cellulose, lignin, detergents, and inorganic substances such as alkali, sulfide and various salts, which is highly polluting.
[0003] Textile printing and dyeing wastewater is characterized by high organic matter concentration, complex composition, deep and variable chromaticity, large pH changes, large changes in water volume and quality, and is difficult to treat industrial wastewater. With the development of chemical fiber fabrics, the rise of imitation silk and the improvement of post-printing and dyeing finishing requirements, a large amount of difficult-to-degrade organic matter such as PVA slurry, rayon alkaline hydrolyzate, new dyes, and auxiliaries have entered the textile printing and dyeing wastewater, posing a serious challenge to traditional wastewater treatment processes. The COD concentration has also increased from hundreds of milligrams per liter to thousands of milligrams per liter.
[0004] At present, the method of treating wastewater by coagulation mainly involves adding inorganic metal salt coagulants and utilizing a series of hydrolysis reactions to form hydrolysis products with various charges and polymerization properties. The hydrolysis products can enhance the binding capacity and improve the coagulation efficiency. However, there are still problems such as large dosage, large sludge discharge, low efficiency in removing small molecular organic matter, and low effluent pH. Summary of the invention
[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is how to simplify the treatment process for wastewater with high turbidity and high organic content, so that the pH value of the effluent changes slowly while improving the coagulation efficiency. To this end, the present invention provides a method for treating textile printing and dyeing wastewater using a rare earth modified Ti-based dry gel coagulant.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] The present invention provides a method for treating textile printing and dyeing wastewater by using a rare earth modified Ti-based dry gel coagulant, comprising the following steps:
[0008] (1) Preparation of rare earth modified Ti-based dry gel coagulant:
[0009] Add the rare earth metal salt to the mixture of ethanol A and acetylacetone, and after it is completely dissolved, add titanium tetrachloride dropwise; then add the mixture of ethanol B and distilled water dropwise, stir evenly, and dry to obtain;
[0010] (2) Add the rare earth modified Ti-based dry gel coagulant into the textile printing and dyeing wastewater, stir and then let it stand.
[0011] Preferably, in step (1), the molar ratio of the rare earth element Re in the rare earth metal salt to the titanium element Ti in titanium tetrachloride is: Re / Ti=(0.01-0.05):1; the molar ratio of acetylacetone (AcAc) to the titanium element Ti in titanium tetrachloride is: AcAc / Ti=1:4; the molar ratio of distilled water H2O to the titanium element Ti in titanium tetrachloride is: H2O / Ti=4:1;
[0012] More preferably, the molar ratio of the rare earth element Re in the rare earth metal salt to the titanium element Ti in titanium tetrachloride is: Re / Ti=0.04:1;
[0013] Among them, the present invention preferably has Re / Ti=(0.01-0.05): 1. If Re / Ti is too low, the proportion of mononuclear and medium polymers increases, while the proportion of colloidal hydrolysates decreases, resulting in poor coagulation efficiency; if Re / Ti is too high, excessive Re will form Re-AcAc complexes through complexation, thereby limiting the polymerization of Re / Ti-based hydrolysates. The present invention plays a vital role in the coagulation mechanism by regulating the Re / Ti ratio, thereby affecting the hydrolysis degree of Re and Ti.
[0014] Preferably, the volume ratio of ethanol A to ethanol B is 2:1; the mixed volume ratio of ethanol B to distilled water is 5:1;
[0015] Preferably, the rare earth metal salt is a rare earth metal nitrate, a rare earth metal hydrochloride or a rare earth metal carbonate;
[0016] More preferably, the rare earth metal salt is a rare earth metal nitrate;
[0017] Among them, due to the different coordination abilities of nitrate ions, carbonate ions, and chloride ions, they exhibit different hydrolysis characteristics, resulting in different performances of the synthesized materials. - and CO3 2- Ti 4+ The coordination capacity is better than NO3 - Once dissolved in water, Ti 4+ The ion quickly coordinates with the H2O molecule and rapidly hydrolyzes to form a mononuclear hydroxyl complex. One of the coordinated H2O molecules is firstly - Substitution, then with hydrolyzed Ti 4+-H2O complexes form bidentate complexes, and then undergo dehydration to form NO3 - Ti-O-Ti cluster. Containing NO3 - The further transformation of the clusters involves two processes: denitrification and dehydration, ultimately forming polymerized Ti-O-Ti clusters.
[0018] Preferably, the rare earth element in the rare earth metal salt is La, Ce, Nd, Y, Sm, Gd, Pr, Eu or Ho;
[0019] More preferably, the rare earth element in the rare earth metal salt is Ho;
[0020] Among them, since the atomic radius of rare earth elements gradually decreases with the increase of atomic number, and holmium has the smallest atomic radius, Ti is more easily incorporated into the framework of Ho hydrolyzate to form Ho-O-Ti bonds. In addition, the flocculant properties show that Ho-Ti gel promotes the formation of flocs with larger particle size and denser structure compared with other Ti-Re gels.
[0021] Preferably, the stirring time is 90 minutes; the drying temperature is 50°C, and the drying is performed until a xerogel of constant weight is obtained;
[0022] Preferably, in step (2), the textile printing and dyeing wastewater is first stirred at a speed of 200-300rpm for 30-40s, and then the rare earth modified Ti-based dry gel coagulant is added to the textile printing and dyeing wastewater, stirred at a speed of 200-300rpm for 1-2min, and then stirred at a speed of 40rpm for 15-20min, and allowed to stand for 20-30min.
[0023] More preferably, in step (2), the textile printing and dyeing wastewater is first stirred at a speed of 200 rpm for 30 seconds, and then the rare earth modified Ti-based dry gel coagulant is added to the textile printing and dyeing wastewater, stirred at a speed of 200 rpm for 1 minute, and then stirred at a speed of 40 rpm for 15 minutes, and allowed to stand for 20 minutes.
[0024] Preferably, the turbidity of the textile printing and dyeing wastewater is ≥35NTU, the pH is 8-12, and the absorbance is UV 254 ≥2.5;
[0025] Preferably, the textile printing and dyeing wastewater is textile wastewater or printing and dyeing wastewater;
[0026] Preferably, when the textile printing and dyeing wastewater is textile wastewater, the mass percentage content of organic matter in the textile wastewater before treatment is ≥80%; the organic matter in the textile wastewater before treatment includes: fulvic acid, humic acid and other organic matter;
[0027] Preferably, when the textile printing and dyeing wastewater is printing and dyeing wastewater, the organic matter in the printing and dyeing wastewater before treatment includes dyes, organic solvents and other organic matter:
[0028] Preferably, the mass ratio of the rare earth modified Ti-based dry gel coagulant to the volume ratio of the textile printing and dyeing wastewater is (0.25-1.05) g: 1 L;
[0029] Preferably, the textile printing and dyeing wastewater is textile wastewater; the mass ratio of the rare earth modified Ti-based dry gel coagulant to the volume ratio of the textile wastewater is (0.8-1.05) g:1L;
[0030] More preferably, the mass ratio of the rare earth modified Ti-based dry gel coagulant to the volume of the textile wastewater is 0.95 g:1 L;
[0031] Among them, the preferred dosage of the present invention is (0.8-1.05) g: 1L. If it is too low, due to insufficient coagulant, it may not be possible to effectively condense suspended solids and colloids, resulting in poor precipitation effect, and the turbidity of the wastewater is not significantly reduced, resulting in substandard effluent water quality; if it is too high, due to excessive coagulant, it may cause too much residual coagulant to enter the wastewater, affecting the efficiency of subsequent treatment links, and may even cause secondary pollution of the water body and increase treatment costs;
[0032] Preferably, the textile printing and dyeing wastewater is printing and dyeing wastewater; the mass ratio of the rare earth modified Ti-based dry gel coagulant to the printing and dyeing wastewater is (0.25-0.45) g:1L.
[0033] More preferably, the mass ratio of the rare earth modified Ti-based dry gel coagulant to the volume of the printing and dyeing wastewater is 0.35g:1L.
[0034] Among them, the preferred dosage of the present invention is (0.25-0.45) g: 1L. If it is too low, due to insufficient coagulant, the dyes and suspended matter in the wastewater may not be effectively removed, resulting in unsatisfactory removal of turbidity and dyeing pollutants in the printing and dyeing wastewater; if it is too high, due to excessive coagulant, the residual substances of the coagulant may increase, which affects the subsequent water treatment steps (such as precipitation and filtration of suspended particles);
[0035] Preferably, when the textile printing and dyeing wastewater is textile wastewater, the turbidity of the treated textile wastewater is ≤0.56NTU, the pH is 6-6.3, and the absorbance UV 254 ≤0.05; the mass percentage content of organic matter in the treated textile wastewater is ≤0.52%;
[0036] Preferably, when the textile printing and dyeing wastewater is printing and dyeing wastewater, the turbidity of the treated printing and dyeing wastewater is ≤15NTU, the pH is 6.2-6.5, and the absorbance UV 254 ≤0.32.
[0037] The technical solution of the present invention achieves the following beneficial technical effects:
[0038] The metal titanium salt coagulant prepared by the present invention is a macromolecular structure formed by polycondensation of titanium hydrolyzate complexed with acetylacetone. Because its rare earth metal has rich energy levels and a special 4f outer electron layer structure, it is easier to combine with organic or inorganic functional groups through coordination bonds to form a compound with multiple valence states and multiple coordination numbers, and it is more advantageous to use it as a reinforcing agent for the coagulant. The present invention selects rare earth metal nitrate as a modifying element, and combines acetylacetone and metal titanium salt, and finally prepares Re-Ti gel coagulant by regulating the molar ratio of rare earth Ho to titanium. The hydrolyzate of the obtained gel coagulant is an amorphous form of incomplete hydrolysis polymerization of titanium; at the same time, by regulating the amount of gel coagulant added in textile printing and dyeing wastewater, the stirring speed and time before and after adding the gel coagulant, etc., the treatment process method of the present invention is more suitable for treating textile printing and dyeing wastewater.
[0039] The treatment method of the present invention has the advantages of simple operation, slow change of effluent pH, high coagulation efficiency, etc., and shows good coagulation performance for textile printing and dyeing wastewater with high turbidity and high organic matter. Experiments show that the composite coagulant prepared by modifying Ti-based dry gel with rare earth metals, compared with a single titanium-based coagulant, the combination of titanium and rare earth metal salts gives full play to the advantages of the two metal coagulants, makes up for the shortcomings of a single metal-based coagulant, and thus gives play to their respective advantages, making the coagulation process applicable to a wider range of water quality conditions, such as textile printing and dyeing wastewater with high turbidity and high organic matter. The use of the sol-gel method to develop a titanium-containing composite coagulant retains the dual advantages of the composite process and the sol-gel method, and the synthesized composite coagulant has good stability and coagulation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The XRD diagrams are of the Ti-Ho dry gel coagulants with different Ho / Ti molar ratios in Example 4 of the present invention and the Ti gel (titanium tetrachloride) in Comparative Example 1. DETAILED DESCRIPTION
[0041] Example 1
[0042] This embodiment provides a method for treating textile printing and dyeing wastewater using a rare earth modified Ti-based dry gel coagulant, comprising the following steps:
[0043] (1) Preparation of rare earth modified Ti-based dry gel coagulant:
[0044] Ti-Re xerogel was prepared by sol-gel method using acetylacetone (AcAc) as hydrolysis inhibitor. The specific process is as follows:
[0045] 0.0011 mol of rare earth metal salt (holmium nitrate) was added to a mixture of ethanol A (20 mL) and acetylacetone. After complete dissolution, 0.028 mol of titanium tetrachloride was added dropwise. Subsequently, a mixture of ethanol B (10 mL) and distilled water was added dropwise. After stirring for 90 minutes, a uniform sol was obtained. The mixture was dried in a vacuum drying oven at 50°C until the sol became a xerogel of constant weight, and then dried and stored.
[0046] The molar ratio of the rare earth element Ho in the rare earth metal salt to the titanium element Ti in titanium tetrachloride is: Ho / Ti=0.04:1; the molar ratio of acetylacetone (AcAc) to the titanium element Ti in titanium tetrachloride is: AcAc / Ti=1:4; the molar ratio of distilled water H2O to the titanium element Ti in titanium tetrachloride is: H2O / Ti=4:1; the volume ratio of ethanol A to ethanol B is 2:1; the mixed volume ratio of ethanol B to distilled water is 5:1;
[0047] (2) At 25 °C, the textile printing and dyeing wastewater was first stirred at a speed of 200 rpm for 30 s, and then the rare earth modified Ti-based dry gel coagulant was added to the textile printing and dyeing wastewater, stirred at a speed of 200 rpm for 1 min, and then stirred at a speed of 40 rpm for 15 min, and then allowed to stand for 20 min.
[0048] Among them, when the textile printing and dyeing wastewater is textile wastewater (such as cotton pulp black liquor), the volume ratio of the mass of the rare earth modified Ti-based dry gel coagulant to the textile wastewater is 0.95g:1L; when the textile printing and dyeing wastewater is printing and dyeing wastewater, the volume ratio of the mass of the rare earth modified Ti-based dry gel coagulant to the printing and dyeing wastewater is 0.35g:1L.
[0049] Among them, the wastewater samples used in this embodiment: cotton pulp black liquor was taken from Alar Zhongtai Textile Technology Co., Ltd., and printing and dyeing wastewater was taken from Alar Xingmeida Printing and Dyeing Co., Ltd. Textile wastewater (cotton pulp black liquor) mainly contains organic matter such as fulvic acid and humic acid, and printing and dyeing wastewater mainly contains a large amount of dyes and organic solvents. Therefore, the absorbance (UV value) at 254nm was measured by ultraviolet visible spectrophotometer. According to UV 254 The water quality index of the actual wastewater (wastewater before treatment) is shown in Table 1.
[0050] Table 1 Water quality indicators
[0051]
[0052] Example 2 Determination of the Type of Acid Ions in Rare Earth Metal Salts
[0053] In order to study the coagulation performance of Ti-Nd synthesized from different neodymium sources, the turbidity removal (turbidity removal rate) and organic matter removal performance (UV 254 The removal rate is shown in Table 2.
[0054] Among them, the preparation method of the Ti-Nd dry gel coagulant synthesized with neodymium nitrate, neodymium chloride and neodymium carbonate is different from step (1) of Example 1 only in that the rare earth metal salt (holmium nitrate) is replaced by neodymium nitrate, neodymium chloride and neodymium carbonate in this embodiment, and the other parameters are the same.
[0055] At 25°C, 300 mL of wastewater sample (cotton pulp black liquor) was taken into a beaker, and the dry gel coagulant prepared in this example was added. After treatment according to the method of step (2) of Example 1, a water sample to be tested was taken with a syringe at 2 cm below the liquid surface after stirring and standing, and the water quality index was measured.
[0056] The water sample to be tested was filtered through a 0.45 μm microporous filter membrane, and the absorbance (UV value) at 254 nm was measured using a UV-visible spectrophotometer. 254 Removal rate = (initial UV 254 -UV after processing 254 ) / Initial UV 254 ×100%.
[0057] The turbidity value was measured by a turbidity meter (direct measurement without filtration treatment), turbidity removal rate (%) = (initial turbidity - turbidity after treatment) / initial turbidity × 100%.
[0058] Table 2 Coagulation properties of Ti-Nd xerogels synthesized with different neodymium sources
[0059] Neodymium Source <![CDATA[UV 254 Removal rate / %]]> Turbidity removal rate / % <![CDATA[Nd(NO3)3]]> 95.0 85.0 <![CDATA[NdCl3]]> 75.0 80.0 <![CDATA[Nd(CO3)3]]> 83.2 87.2
[0060] The turbidity and organic matter removal rate of Ti-Nd synthesized from neodymium nitrate are higher than those of Ti-Nd synthesized from neodymium chloride and neodymium carbonate. At the same dosage, the turbidity removal efficiency of Ti-Nd with neodymium nitrate source is 11.8% and 20% higher than that of Ti-Nd with neodymium carbonate source and neodymium chloride source, and the organic matter removal rate is 4.78% and 5.0% higher. The reason for the difference may be that the coordination ability of nitrate ions, carbonate ions and chloride ions is different, which makes the performance of the synthesized materials different. Therefore, nitrate rare earth metals are used as rare earth sources to synthesize lanthanide gel coagulants.
[0061] Example 3 Determination of rare earth ion species in rare earth metal salts
[0062] In this embodiment, nitrate-based light rare earth metals (La, Ce, Nd, Y, Sm, Gd, Pr, Eu) and nitrate-based heavy rare earth metals (Ho) are used to modify the Ti-based dry gel (TXC).
[0063] Among them, the method for modifying TXC is different from step (1) of Example 1 only in that the rare earth metal salts in this embodiment are nitrate light rare earth metals (La, Ce, Nd, Y, Sm, Gd, Pr, Eu) and nitrate heavy rare earth metals (Ho), and the other parameters are the same.
[0064] Under the condition of 25°C, 300 mL of wastewater sample (cotton pulp black liquor) was taken into a beaker, and the dry gel coagulant prepared in this example was added. After treatment according to the method of step (2) of Example 1, the water sample to be tested was taken with a syringe at 2 cm below the liquid surface after stirring and standing, and the water quality index was measured. The results are shown in Table 3.
[0065] Table 3 Coagulation properties of different Ti-Re xerogels
[0066] Type of coagulant <![CDATA[UV 254 Removal rate / %]]> Turbidity removal rate / % Y-TXC 79.2 78.0 Pr-TXC 90.2 82.0 Eu-TXC 91.7 82.5 Gd-TXC 93.0 83.0 Nd-TXC 95.0 85.0 Ce-TXC 95.6 87.3 Sm-TXC 96.6 87.7 La-TXC 98.3 88.7 Ho-TXC 98.8 98.5
[0067] The experimental results show that the prepared Ti-Re dry gel coagulants can significantly improve the coagulation effect. Except for the Ti-Y dry gel prepared by yttrium nitrate, the coagulation efficiency is above 90%. As the atomic radius of rare earth elements gradually decreases with the increase of atomic number, holmium has the smallest atomic radius. Therefore, Ti is more easily incorporated into the framework of Ho hydrolyzate to form Ho-O-Ti bonds. In addition, the flocculant properties show that Ho-Ti gel promotes the formation of flocs with larger particle size and denser structure compared with other Re-Ti gels. Among them, the turbidity removal rate of the coagulant Ti-Ho after the rare earth metal holmium and titanium are composited is 98.5%, and the removal rate of organic matter is 98.8%. Compared with other rare earth metal modified TXC, it has the best coagulation performance. Therefore, the dry gel Ti-Ho of rare earth metal Ho modified TXC was selected to optimize the raw material ratio experiment.
[0068] Example 4 Determination of Ho / Ti molar ratio
[0069] The method for preparing the Ti-Ho dry gel coagulant in this embodiment is different from step (1) of Example 1 only in that the molar ratio of the rare earth element Ho in the rare earth metal salt to the titanium element Ti in titanium tetrachloride in this embodiment is: Ho / Ti=(0.01-0.05):1 (see Table 4 for details), and the other parameters are the same as step (1) of Example 1.
[0070] ① Under 25°C, 300 mL of wastewater sample (cotton pulp black liquor) was taken into a beaker, and the Ti-Ho dry gel coagulant prepared in this example was added. After treatment according to the method of step (2) of Example 1, a water sample to be tested was taken with a syringe at 2 cm below the liquid surface after stirring and standing, and the water quality index was measured. The results are shown in Table 4.
[0071] ② Under 25°C, 300 mL of wastewater sample (printing and dyeing wastewater) was taken into a beaker, and the Ti-Ho dry gel coagulant prepared in this example was added. After treatment according to the method of step (2) of Example 1, the water sample to be tested was taken with a syringe at 2 cm below the liquid surface after stirring and standing, and the water quality index was measured. The results are shown in Table 5.
[0072] Table 4 Coagulation performance of Ti-Ho xerogels prepared with different Ho / Ti molar ratios on cotton pulp black liquor
[0073] Ho / Ti molar ratio <![CDATA[UV 254 Removal rate / %]]> Turbidity removal rate / % 0.01 90.8 71.5 0.02 93.1 84.2 0.03 97.8 89.7 0.04 98.8 98.5 0.05 93.9 89.5
[0074] Table 5 Coagulation performance of Ti-Ho xerogels prepared with different Ti / Ho molar ratios on printing and dyeing wastewater
[0075] Ho / Ti molar ratio <![CDATA[UV 254 Removal rate / %]]> Turbidity removal rate / % 0.01 79.6 61.2 0.02 83.7 74.2 0.03 87.2 79.6 0.04 88.8 82.3 0.05 83.9 79.5
[0076] According to Table 4, as the Ho / Ti molar ratio increases, the coagulation efficiency is improved. When the Ho / Ti molar ratio is 0.04, the coagulation efficiency reaches the highest turbidity removal rate of 98.5%, and the organic matter removal rate is 98.8%. As the molar ratio continues to increase, the coagulation efficiency decreases, and the optimal Ho / Ti molar ratio is 0.04. Analysis shows that the Re content will affect the hydrolysis and polymerization process of Ti and Re. If Re / Ti is too low, the proportion of mononuclear and medium polymers increases, while the proportion of colloidal hydrolysates decreases, resulting in poor coagulation efficiency; if Re / Ti is too high, the excess Re will form Re-AcAc complexes through complexation, thereby limiting the polymerization of Re / Ti-based hydrolysates. The present invention plays a vital role in the coagulation mechanism by regulating the Re / Ti ratio, thereby affecting the degree of hydrolysis of Re and Ti.
[0077] According to Table 5, with the increase of Ti-Ho molar ratio, the coagulation efficiency is improved, which is more obvious in the color removal. The dye particles are removed. When the Ti-Ho molar ratio is 0.04, the coagulation efficiency reaches the highest turbidity removal rate of 82.3%, and the organic matter removal rate is 88.8%. With the continuous increase of the molar ratio, the coagulation efficiency decreases, and the optimal Ti-Ho molar ratio is 0.04.
[0078] Figure 1The XRD diagrams of Ti-Ho dry gel coagulants with different Ho / Ti molar ratios in this embodiment and Ti gel (titanium tetrachloride) in Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the composite Ti-Ho dry gel did not significantly change the basic structure of the titanium gel. The XRD analysis results proved that the hydrolyzate structure after composite was the same and still showed an amorphous structure. The XRD spectra contained a broad Ti-O structure peak located at 2θ=5°.
[0079] In summary, different wastewater components have different reactivity to coagulants. Due to the different molecular structures and reaction characteristics of pollutants in cotton pulp black liquor and printing and dyeing wastewater, the same coagulant has different UV properties when treating these two types of wastewater. 254 The removal rate and turbidity removal rate show differences. The cotton pulp black liquor produced by the textile industry usually contains organic substances such as fulvic acid and humic acid. These substances have strong colloidal properties and are easily removed by potential neutralization, adsorption and coagulation with coagulants; while for printing and dyeing wastewater containing dyes, the dyes and coagulants are mainly removed by charge neutralization and adsorption. At the same time, in order to better treat wastewater, the coagulation effect can be further improved by optimizing the coagulation conditions. For different types of textile printing and dyeing wastewater, appropriate adjustment of these parameters can ensure that the optimal performance of the coagulant is fully utilized.
[0080] Example 5 Determination of the dosage of Ti-Ho dry gel coagulant
[0081] The method for preparing the Ti-Ho dry gel coagulant in this embodiment is the same as step (1) of embodiment 1, and the difference from embodiment 1 is that when treating cotton pulp black liquor, the mass ratio of the Ti-Ho dry gel coagulant to the volume ratio of the cotton pulp black liquor in step (2) of this embodiment is (0.8-1.05) g: 1 L (see Table 6 for details); when treating printing and dyeing wastewater, the mass ratio of the Ti-Ho dry gel coagulant to the volume ratio of the printing and dyeing wastewater is 0.25-0.45 g: 1 L (see Table 7 for details), and the other parameters are the same;
[0082] ① Under 25°C, 300 mL of wastewater sample (cotton pulp black liquor) was placed in a beaker, and the dosage of this embodiment was followed. Other process parameters were the same as those in step (2) of embodiment 1. After treatment, a syringe was used to take the water sample 2 cm below the liquid surface after stirring and standing for water quality index determination. The results are shown in Table 6.
[0083] ② Under 25°C, 300 mL of wastewater sample (printing and dyeing wastewater) was taken in a beaker, and the dosage of this embodiment was followed. Other process parameters were the same as those in step (2) of embodiment 1. After treatment, a syringe was used to take the water sample 2 cm below the liquid surface after stirring and standing for treatment, and the water quality index was measured. The results are shown in Table 7.
[0084] Table 6 Coagulation performance of cotton pulp black liquor with different dosages of Ti-Ho dry gel
[0085] Dosage / (g / L) <![CDATA[UV 254 Removal rate / %]]> Turbidity removal rate / % 0.8 10.0 12.5 0.85 91.9 92.9 0.9 96.6 97.0 0.95 98.8 98.5 1 96.9 97.4 1.05 96.6 97.1
[0086] Table 7 Coagulation performance of different dosages of Ti-Ho dry gel on printing and dyeing wastewater
[0087] Dosage / (g / L) <![CDATA[UV 254 Removal rate / %]]> Turbidity removal rate / % 0.25 40.0 52.5 0.30 71.9 72.9 0.35 88.8 82.3 0.40 78.8 78.5 0.45 72.9 75.4
[0088] According to Table 6, as the dosage of coagulant increases, the coagulation efficiency increases. When the dosage of coagulant is 0.95g, the coagulation effect reaches the best. If the coagulant is further increased, the coagulation efficiency decreases. 0.95g is the optimal dosage.
[0089] According to Table 7, as the dosage of coagulant increases, the coagulation efficiency increases. When the dosage of coagulant is 0.35g, the coagulation effect reaches the best. If the coagulant is continued to be increased, the coagulation efficiency decreases. 0.35g is the optimal dosage.
[0090] Analysis shows that if the dosage is insufficient, it will not be enough to bridge the organic matter, and some suspended particles will not be affected by the coagulant and remain in a suspended state, resulting in poor coagulation effect; if the dosage is too high, the suspended particles will undergo electrical reversal due to the excessive adsorption of coagulant, which may cause the colloid to stabilize again. On the other hand, the adsorption surface of the suspended particles will be covered by the coagulant, resulting in a "colloid protection" effect that reduces the coagulation effect.
[0091] Example 6 Study on pH of treated water samples
[0092] The method for preparing the Ti-Ho dry gel coagulant in this embodiment is different from step (1) of embodiment 1 only in that the molar ratio of the rare earth element Ho in the rare earth metal salt to the titanium element Ti in titanium tetrachloride in this embodiment is: Ho / Ti=(0.01-0.05):1 (see Table 8 for details), and the other parameters are the same as step (1) of embodiment 1. When treating cotton pulp black liquor, the mass ratio of the Ti-Ho dry gel coagulant in step (2) of this embodiment to the volume ratio of cotton pulp black liquor is (0.8-1.05) g:1 L (see Table 8 for details), and the other parameters are the same as step (2) of embodiment 1.
[0093] Under the condition of 25°C, 300 mL of wastewater sample (cotton pulp black liquor) was taken into a beaker, and the dosage of this embodiment was followed. Other process parameters were the same as those in step (2) of embodiment 1. After treatment, a water sample to be tested was taken with a syringe at a position 2 cm below the liquid surface after stirring and standing. The pH of the treated water sample was measured. The results are shown in Table 8.
[0094] Table 8 Changes in pH of the effluent from Ti-Ho xerogels prepared with different Ho / Ti molar ratios
[0095]
[0096] It can be seen from Table 8 that the pH of the actual wastewater after coagulation at the optimal dosage of the coagulants prepared with different molar ratios is stable at 6.0-6.3, which is basically weakly acidic. In addition, the pH of Ti-Ho after coagulation does not decrease significantly, avoiding the corrosion problem caused by low pH.
[0097] Example 7 Stability Test of Ti-Ho Xerogel Coagulant
[0098] According to the method for treating cotton pulp black liquor in Example 1, the coagulation performance of the Ti-Ho dry gel coagulant obtained in Example 1 was tested for three months. The results are shown in Table 9.
[0099] Table 9 Effect of time on the coagulation performance of cotton spinning black liquor treated with Ti-Ho dry gel coagulant
[0100] time <![CDATA[UV 254 Removal rate / %]]> Turbidity removal rate / % 1day 98.8 98.5 2days 98.8 98.5 4days 98.6 98.4 8days 98.1 98.0 16days 98.0 98.0 32days 97.5 97.0 64days 97.0 96.0 90days 95.1 94.5
[0101] In summary, the wastewater treated by the method of the present invention complies with the "Integrated Wastewater Discharge Standard" (GB 8978-1996) and the "Textile Dyeing and Finishing Industry Water Pollutant Discharge Standard" (GB 4287-2012).
[0102] Comparative Example 1
[0103] This comparative example provides a Ti-based dry gel coagulant, comprising the following steps:
[0104] To a mixture of ethanol A (20 mL) and acetylacetone, add 0.028 mol of titanium source (titanium tetrachloride, n-butyl titanate, isobutyl titanate or titanium sulfate); then add a mixture of ethanol B (10 mL) and distilled water, stir for 90 minutes, and obtain a uniform sol; dry in a vacuum drying oven at 50°C until the sol becomes a xerogel of constant weight, and then store it dry.
[0105] Among them, the molar ratio of acetylacetone AcAc to titanium element Ti in titanium tetrachloride is: AcAc / Ti=1:4; the molar ratio of distilled water H2O to titanium element Ti in titanium tetrachloride is: H2O / Ti=4:1; the volume ratio of ethanol A and ethanol B is 2:1; the mixed volume ratio of ethanol B and distilled water is 5:1.
[0106] ① Under 25°C, 300 mL of wastewater sample (cotton pulp black liquor) was taken into a beaker, and different Ti-based dry gel coagulants prepared in this comparative example were added respectively. After treatment according to the method of step (2) of Example 1, the water sample to be tested was taken with a syringe at 2 cm below the liquid surface after stirring and standing, and the water quality index was measured. The results are shown in Table 10.
[0107] ② Under 25°C, 300 mL of wastewater sample (printing and dyeing wastewater) was taken into a beaker, and different Ti-based dry gel coagulants prepared in this comparative example were added respectively. After treatment according to the method of step (2) of Example 1, the water sample to be tested was taken with a syringe at 2 cm below the liquid surface after stirring and standing, and the water quality index was measured. The results are shown in Table 11.
[0108] Table 10 Coagulation performance of different titanium-based dry gel coagulants on cotton spinning black liquor
[0109] Different titanium sources <![CDATA[UV 254 Removal rate / %]]> Turbidity removal rate / % Outlet pH Titanium Tetrachloride 70.0 42.5 5.0 Butyl Titanate 41.9 22.9 4.9 Isobutyl Titanate 58.8 32.3 4.8 Titanium sulfate 62.4 38.5 4.9
[0110] Table 11 Coagulation performance of different titanium-based dry gel coagulants on printing and dyeing wastewater
[0111] Different titanium sources <![CDATA[UV 254 Removal rate / %]]> Turbidity removal rate / % Outlet pH Titanium Tetrachloride 65.0 40.5 5.2 Butyl Titanate 34.9 20.2 5.1 Isobutyl Titanate 45.8 30.9 5.0 Titanium sulfate 58.4 36.5 5.0
[0112] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A method for treating textile printing and dyeing wastewater using a rare earth modified Ti-based dry gel coagulant, characterized in that: The following steps are involved: (1) Preparation of rare earth modified Ti-based dry gel coagulant: Add the rare earth metal salt to the mixture of ethanol A and acetylacetone, and after it is completely dissolved, add titanium tetrachloride dropwise; then add the mixture of ethanol B and distilled water dropwise, stir evenly, and dry to obtain; (2) Add the rare earth modified Ti-based dry gel coagulant into the textile printing and dyeing wastewater, stir and then let it stand.
2. The method according to claim 1, characterized in that In step (1), the molar ratio of the rare earth element Re in the rare earth metal salt to the titanium element Ti in titanium tetrachloride is: Re / Ti=(0.01-0.05):
1.
3. The method according to claim 2, characterized in that In step (1), the molar ratio of the rare earth element Re in the rare earth metal salt to the titanium element Ti in titanium tetrachloride is: Re / Ti=0.04:
1.
4. The method according to claim 1, characterized in that The rare earth metal salt is a rare earth metal nitrate, a rare earth metal hydrochloride or a rare earth metal carbonate; the rare earth element in the rare earth metal salt is La, Ce, Nd, Y, Sm, Gd, Pr, Eu or Ho.
5. The method according to claim 4, characterized in that The rare earth metal salt is rare earth metal nitrate; the rare earth element in the rare earth metal salt is Ho.
6. The method according to claim 1, characterized in that In step (1), the molar ratio of acetylacetone AcAc to the titanium element Ti in titanium tetrachloride is: AcAc / Ti=1:4; the molar ratio of distilled water H2O to the titanium element Ti in titanium tetrachloride is: H2O / Ti=4:1; The volume ratio of ethanol A to ethanol B is 2:1; the mixed volume ratio of ethanol B to distilled water is 5:1; the stirring time is 90 minutes; the drying temperature is 50°C, and the drying is performed until a dry gel of constant weight is obtained.
7. The method according to claim 1, characterized in that In step (2), the textile printing and dyeing wastewater is first stirred at a speed of 200-300 rpm for 30-40 seconds, and then the rare earth modified Ti-based dry gel coagulant is added to the textile printing and dyeing wastewater, stirred at a speed of 200-300 rpm for 1-2 minutes, and then stirred at a speed of 40 rpm for 15-20 minutes, and allowed to stand for 20-30 minutes.
8. The method according to claim 1, characterized in that In step (2), the textile printing and dyeing wastewater is textile wastewater or printing and dyeing wastewater; the mass ratio of the rare earth modified Ti-based dry gel coagulant to the volume ratio of the textile printing and dyeing wastewater is (0.25-1.05) g:1L.
9. The method according to claim 8, characterized in that In step (2), when the textile printing and dyeing wastewater is textile wastewater, the mass ratio of the rare earth modified Ti-based dry gel coagulant to the volume of the textile wastewater is (0.8-1.05) g: 1 L; Or, when the textile printing and dyeing wastewater is printing and dyeing wastewater, the mass ratio of the rare earth modified Ti-based dry gel coagulant to the volume of the printing and dyeing wastewater is (0.25-0.45) g:1L.
10. The method according to claim 8, characterized in that In step (2), the turbidity of the textile printing and dyeing wastewater before treatment is ≥35NTU, the pH is 8-12, and the absorbance UV 254 ≥2.5; When the textile printing and dyeing wastewater is textile wastewater, the turbidity of the treated textile wastewater is ≤0.56NTU, the pH is 6-6.3, and the absorbance is UV 254 ≤0.05; or, when the textile printing and dyeing wastewater is printing and dyeing wastewater, the turbidity of the treated printing and dyeing wastewater is ≤15NTU, the pH is 6.2-6.5, and the absorbance UV 254 ≤0.32.
Citation Information
Patent Citations
TiO2-based coagulant and use thereof
CN104944547A
Preparation method of coagulant for removing disperse dye wastewater
CN105174400A
Polyaluminum chloride titanium inorganic composite coagulant and preparation method and application thereof
CN109292936A
Fluorine or phosphorus-containing water treatment equipment
JP2004148289A
Method for Phosphorus Removal from Waste Water Using Poly Titanium Coagulant
KR1020180003288A